The emergence of reflexive global labour law; Die Herausbildung eines reflexiven globalen Arbeitsrechts - Ralf Rogowski (Industrielle Beziehungen, 2015)
The article introduces the main tenets of reflexive labour law and uses this perspective to interpret core trends in global labour law. It suggests a conceptual distinction between international and global labour law and identifies a transformation in the global labour law regime related to processes of reflexivity and constitutionalisation. The first part of the article analyses reflexivity within the International Labour Organization (ILO) in relation to its policy of defining labour standards as human rights. It interprets the increasing attention given to soft law in the ILO as a reflexive response to the globalisation of labour law outside the confines of the nation state. The core reflexive law concept of regulation of self-regulation is applied to analyse a key source of global labour law, namely codes of conduct regulating corporate citizenship and corporate social responsibility programmes in multinational companies. In the final section, the article argues that global labour law is emerging as a separate regime in the world society and comments on constitutionalisation as a key process in the emerging regime of global labour law. – – Der Artikel stellt Grundannahmen des reflexiven Arbeitsrechts vor und verwendet diese Perspektive zur Analyse des globalen Arbeitsrechts. Er schlägt eine konzeptionelle Unterscheidung zwischen internationalem und globalem Arbeitsrecht vor und beschreibt die Transformation des globalen Arbeitsrechtregimes mit Hilfe der Konzepte Reflexivität und Konstitutionalisierung. Der Artikel stellt Reflexivität innerhalb der Internationalen Arbeiterorganisation (ILO) fest, zum Beispiel in Bezug auf die Politik der Priorisierung bestimmter Arbeitsbedingungen als Menschenrechte. Die zunehmende Nutzung sog. soft law Instrumente in der ILO wird als reflexive Rechtsstrategie gedeutet, die auf die Globalisierung des Arbeitsrechts außerhalb der Grenzen des Nationalstaats antwortet. Das reflexivrechtliche Kernkonzept der Regulierung von Selbstregulierung wird angewendet in der Analyse einer zentralen Quelle des globalen Arbeitsrechts, der sog. codes of conduct oder Unternehmenskodexe, die Corporate Social Responsibility (CSR) und andere Programme zur sozialen Verantwortung der multinationalen Unternehmen regulieren. Im abschließenden Abschnitt diskutiert der Artikel, inwieweit globales Arbeitsrecht als autonomes Regime in der Weltgesellschaft verstanden werden kann, das sich durch Konstitutionalisierung stabilisiert.
Keywords: G34; J80; K31; K40; M14; 330; global labour law; reflexive labour law; codes of conduct; corporate social responsibility; corporate citizenship